Political marketing and management in Ghana : a new architecture - Mensah, Kobby A. (Springer International Publishing, 2017)
'[This book] offers ground-breaking research into political marketing and management in a developing democracy, significantly broadening our understanding of how business concepts and techniques permeate politics in different circumstances. Covering a range of topics including political HR and branding in parties, it lays important foundations for new political marketing and management research.' --Jennifer Lees-Marshment, Professor, The University of Auckland, New Zealand 'A pace-setting book on political marketing in Ghana that offers a strategic direction to political campaigning, financing, human resource management and leadership.' --Joshua Yindenaba Abor, Professor and Dean, The University of Ghana Business School, University of Ghana This book focuses on the emergence of new frames of political engagement underpinned by concepts in marketing, management, and organisation. It goes beyond political electioneering and campaigning and considers business theories such as market research, segmentation, social media, brand architecture, and human resources. With contributions from a range of skilled experts, Political Marketing and Management in Ghana emphasises and provides insights on the symbols-oriented approach of political campaigning in Africa, and distinguishes this from the technology-driven process of the west. Offering a total understanding of African politics and its supply and demand interactivity between key actors, this book is of great use to academics interested in political science, communications, marketing, and business and management.
Keywords: Politics, Practical -- Ghana.; Marketing -- Political aspects -- Ghana.; Ghana -- Politics and government.; Ghana.; elektronické knihy; electronic books